Quarter Life Crisis pada Dewasa Muda: Peran Orientasi Ekspektasi Masa Depan dan Keberfungsian Keluarga - Supriyati, Supriyati; Rahman, Puspa Rahayu Utami; Aisha, Dinda (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to investigate the influence of future expectation orientation and family functioning on quarter-life crisis among young adults in Karawang Regency. The research employs a quantitative method with a causal design. Participants consist of 204 young adults aged 18 to 25 years residing in Karawang Regency, comprising 71 males and 133 females. Sampling was conducted using the convenience sampling technique. Data collection utilized three psychological scales: the Quarter Life Crisis Scale, the Education and Work Future Expectation Scale, and the Family Function Scale. Data analysis techniques included normality test, linearity test, multiple regression analysis, and categorization test. The results indicate that future expectation orientation and family functioning significantly influence quarter-life crisis among young adults in Karawang Regency. The combined influence of future expectation orientation and family functioning on quarter-life crisis is 3.9%, with the remaining variance attributed to other unexamined factors.